Efektivitas Model Pembelajaran Project Based Learning Terhadap Minat Belajar Siswa Pada Materi Bola Voli di Kelas X SMAN 7 Mataram - Yuni Amirta Nadila; Balkis Ratu Nurul Laela Esser; Kokom Supriyatnak (Jurnal Porkes, 2026)
The main problem in this study is the low level of student participation and enthusiasm in Physical Education, Sports, and Health (PJOK) classes covering volleyball at Mataram State High School 7. Based on initial observations, most students exhibited passive attitudes, a lack of motivation, and a fear of performing basic technical movements. This study aims to determine the effectiveness of the Project-Based Learning (PjBL) model on students’ interest in learning volleyball. A quantitative approach was used with a one-shot case study design. The study population consisted of all 282 tenth-grade students, with a sample of 35 students from Class XE selected through purposive sampling. The main instrument was a Likert-scale learning interest questionnaire that had been tested for validity and reliability, supplemented by an observation sheet. Data analysis used descriptive statistics based on percentages. The results of the study show that the average percentage of students’ learning interest reached 83.84%, which falls into the “very high” category. All interest indicators namely, curiosity, engagement, understanding, enjoyment, collaboration, and motivation were in the “very high” category. The enjoyment indicator received the highest score at 86.47%, followed by motivation at 84.85%, and collaboration at 84.28%. The conclusion of this study is that the PjBL learning model has been proven effective in increasing students’ interest in learning volleyball-related material.